2016
DOI: 10.3892/ol.2016.4274
|View full text |Cite
|
Sign up to set email alerts
|

CDH1 promoter methylation correlates with decreased gene expression and poor prognosis in patients with breast cancer

Abstract: Abstract. The E-cadherin gene (CDH1) is associated with poor prognosis and metastasis in patients with breast cancer, and methylation of its promoter is correlated with decreased gene expression. However, there is currently no direct evidence that CDH1 promoter methylation indicates poor prognosis in patients with breast cancer. In the present study, methylation-specific polymerase chain reaction (PCR) was applied to detect the methylation status of the CDH1 promoter in 137 primary breast cancer, 85 matched no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 41 publications
4
39
1
1
Order By: Relevance
“…Our study indicated that the CDH1 methylation rate in CXPA was 67.57% (25/37). This rate is similar to that of many other tumors, including primary lung cancer (88%) (30), breast carcinoma (65-95%) (7,10,31,32) and colorectal carcinoma (52%) (33). We found that DNA methylation preferentially occurred in the first four CpG islands compared with the other CpG islands.…”
Section: Discussionsupporting
confidence: 86%
“…Our study indicated that the CDH1 methylation rate in CXPA was 67.57% (25/37). This rate is similar to that of many other tumors, including primary lung cancer (88%) (30), breast carcinoma (65-95%) (7,10,31,32) and colorectal carcinoma (52%) (33). We found that DNA methylation preferentially occurred in the first four CpG islands compared with the other CpG islands.…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, CDH1 , which encodes the cell adhesion protein E-cadherin, is an important TSG 55. Studies have shown that loss of CDH1 expression by promoter hypermethylation is involved in several types of cancer, including colorectal,56 lung,57 breast,23 and gastric cancers 58. This meta-analysis was done to resolve some of the inconsistent reports of the association between CDH1 promoter methylation and HNSCC 15,16…”
Section: Discussionmentioning
confidence: 99%
“…There has been increasing evidence showing that loss of CDH1 expression is involved in tumor cell invasion and metastasis in cancer, including HNSCC 20–22. Several studies have found that promoter methylation of CDH1 may lead to transcriptional inactivation of CDH1 and that this mechanism is involved in several types of malignancy, including breast,23 gastric,24 and colorectal cancers,25 and HNSCC 26,27…”
Section: Introductionmentioning
confidence: 99%
“…Two markers were both significantly associated with poor and improved outcome in separate studies [54,75,78,91]. Five markers showed a significant relation to poor outcome in one study, while other studies looking into the same marker found no correlation [44,57,58,65,83]. Finally, four markers showed no significant relation to disease outcome in any study [48,63,66,68,70,88,92,95].…”
Section: Prognostic Marker Findingsmentioning
confidence: 91%
“…Two alternative promotor sites were analysed in these studies; for both alternative promotors, significant correlation to poor survival was found. Three studies reported on CDH1 methylation in relation to disease outcome [49,50,58]. Two studies identified a statistically significant correlation between CDH1 hypermethylation and poor disease outcome.…”
Section: Prognostic Marker Findingsmentioning
confidence: 99%